Maritime Security Sustainability: Analyzing Regulations And Policies In The Southeast Asian Maritime Region - Arya Pradana, Dimas Gading; Yusnaldi; Rudiyanto (International Journal of Education, Vocational and Social Science, 2025)
This study examines the governance, legislation, and policies influencing maritime security in Southeast Asia, with a focus on sustainability. It explores the effectiveness of regional and national frameworks, legal enforcement, and international cooperation in addressing maritime threats such as piracy, illegal fishing, and territorial disputes. Despite significant progress in policy development and regional initiatives, the implementation of maritime security measures remains fragmented and inconsistent across the region. Key challenges include limited inter-country coordination, resource constraints, and weak enforcement mechanisms. However, increasing recognition of the interlinkages between environmental sustainability and maritime security is evident in several national policies. The study highlights the need for stronger multilateral cooperation, enhanced law enforcement, and the integration of sustainable practices into maritime policies. It concludes with recommendations to improve regional coordination, strengthen enforcement capacities, and address socio-economic drivers of maritime insecurity to achieve long-term sustainability in Southeast Asia’s maritime security